Animal Waste Policy Innovation - Muliawaty, Lia; Ruyani, Nyi Raden; Nana Nasuha, Cecep (Publica: Jurnal Pemikiran Administrasi Negara, 2025)
Animal waste management in Kuningan Regency, especially in Cipari Village, faces serious challenges in the form of environmental pollution, low awareness of livestock farmers, and suboptimal existing policies. This study aims to analyze innovations in animal waste management policies with a participatory and collaborative approach. The method used is descriptive qualitative with data collection techniques through in-depth interviews, document studies, and field observations. The results of the study indicate that the implementation of policy innovations based on three main principles, namely creation of interactive value, distributed co-creation, and mass collaboration, has encouraged multi-party involvement in overcoming waste problems. The findings show real collaboration between livestock farmers, local governments, academics, and the private sector, which results in the practice of processing waste into organic fertilizer and biogas. However, implementation is still hampered by the lack of incentives, technological infrastructure, and coordination between institutions. Therefore, the strategy for increasing policy effectiveness is directed at institutional integration, ongoing education, incentives for small farmers, and strengthening waste management cooperatives. This study provides a conceptual contribution to collaborative and practical governance for the development of environmentally friendly agriculture.